2008
DOI: 10.1007/s11605-008-0658-9
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Results of Reversal of Vertical Banded Gastroplasty (VBG)

Abstract: We conclude that reversal of a VBG results in symptomatic relief in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Revisional surgery is associated with a high rate of symptomatic resolution. Thoreson et al found that symptom resolution rates were high in 27 patients to undergo reversal of VBG via gastrogastrostomy (89% symptom improvement) [10]. Contrary to our findings, after 32 months follow-up significant weight gain was not observed in these patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Revisional surgery is associated with a high rate of symptomatic resolution. Thoreson et al found that symptom resolution rates were high in 27 patients to undergo reversal of VBG via gastrogastrostomy (89% symptom improvement) [10]. Contrary to our findings, after 32 months follow-up significant weight gain was not observed in these patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, GERD is the most frequent cause for reversal surgery: In a recent analysis on patients who underwent a reversal of a VBG [24], the rate of reflux as presenting symptom was 67%. The conversion into Roux-en-Y gastric bypass is an effective technique for VBG patients who suffered from GERD: In a study on 25 patients with severe GERD after VBG who subsequently underwent a conversion to a gastric bypass, 96% of the patients were symptom free after the surgical conversion at a mean follow-up of 37 months [25].…”
Section: Discussionmentioning
confidence: 99%
“…Even accounting for cases where technical difficulty was encountered, the mean operating time in our series was 50 minutes. Laparoscopic reversal may be sufficiently challenging that open revision remains popular [7]. creating disorientation as seen in one of our cases in the series.…”
Section: Discussionmentioning
confidence: 86%